Butterflies (Lepidoptera - Rhopalocera) of coastal areas of Southern West Bengal, India - Payra, Arajush (Academia Journal of Biology, 2017)
The present study was carried out to prepare a checklist of butterflies in the Coastal areas of Purba Medinipur District of southern West Bengal between January 2014 and February 2016. A total of 112 butterfly species belonging to 74 genera under 14 subfamilies and five families were recorded during the study period. Nymphalidae and Lycaenidae were the most dominant family, whereas Papilionidae was the least dominant family. Among 112 butterfly species recorded, 9 species were legally protected under the Wildlife (Protection) Act, 1972. A total of 59 species were newly recorded in the study area. Suastus minuta Moore, 1877 was recorded for the first time in West Bengal. The present results also provide a detailed comparison of butterfly diversity among different studies conducted in southern West Bengal. Citation: Payra A., Mishra R. K., Mondal K., 2017. Butterflies (Lepidoptera - Rhopalocera) of coastal areas of Southern West Bengal, India. Tap chi Sinh hoc, 39(3): 276-390. DOI: 10.15625/0866-7160/v39n3.9243. Received 21 February 2017, accepted 10 March 2017 *Corresponding author: arajushpayra@gmail.com